Analisis Tindak Tutur Representatif dalam Unggahan Video Edukasi Sains pada Saluran Media Sosial Youtube Fajrul Fx - Ajeng Ayuningdyas; Laksmana Pujiatmoko; Mega Wahyu Ningrum; M. Farell Rachmadhani Zidan Saputra; Tri Widiyanto; Asep Purwo Yudi Utomo; Haris Kurnianto; Eko Ahmad Riyanto (Student Research Journal, 2025)
This study aims to analyze representative speech acts in science education videos on the Fajrul Fx YouTube channel. This video was chosen due to its delivery characteristics that combine elements of science and entertainment, which are considered engaging by viewers. The method used in this study is descriptive qualitative with a pragmatic approach. The research data consists of transcripts from six science education videos, which were analyzed to identify the types of representative speech acts used. The results show that there are 461 representative speech acts in the videos, with the types of speech acts found including stating, acknowledging, reporting, claiming, suggesting, mentioning, complaining, informing, indicating, and speculating. This analysis provides insights into the communication strategies used to convey science material and can contribute to content creators in designing more effective educational videos. The researchers hope that with a deeper understanding of proper language use, students can improve their communication skills and develop knowledge of representative speech acts in the future.